Assessing Constitutional Frameworks for Closed Proportional Representation in House of Representatives Elections - Vemansyah Simatupang; Bariyima Sylvester Kokpan (Jurnal Mengkaji Indonesia, 2023)
Abstract: The electoral system in Indonesia has implemented two politically different systems, one of which is the proportional system. This proportional system is also divided into proportional with an open list and proportional with a closed list. The basic idea of ​​a proportional system is that the composition of seats obtained by a political party in an electoral area will be in balance with the proportion of votes received by the political party concerned in the election. Even in this system, only a few votes are wasted. According to the provisions of Article 168 paragraph (2) of Law No. 7/2017, the electoral system for DPR members is open proportional with a majority vote. This system has a good level of representation because the people are free to determine their representatives who will sit in Parliament directly and can continue to supervise those they choose. Purpose: This research aims to analyze the application of a closed proportional system in the DPR election from the perspective of the 1945 Constitution of the Republic of Indonesia; arrangements regarding the principles of elections in the constitution are regulated in Article 22E of the 1945 Constitution of the Republic of Indonesia. Design/Methodology/Approach: The type of research used in this research is normative legal research, using statute and conceptual approaches. Findings: The results of this research indicate that the application of a closed proportional system is not following the Constitution of the Republic of Indonesia because it will close space for the people to make their own choices directly because in a closed proportional system the determination of who are the candidates for members of the DPR  who will sit in parliament is absolute political party wishes. Originality/Value: Debates about the constitutionality of open proportional and closed proportional systems always fill public spaces, especially before the election. Due to this issue, a fundamental question arises about whether the closed proportional system in the election of DPR members follows the Constitution of the Republic of Indonesia. This issue is the reason for research regarding the general election system for DPR members following the Constitution of the Republic of Indonesia.